Spillovers of Innovation Activities and Their Profitability - Dirk Czarnitzki; Kornelius Kraft (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2007)
Knowledge spillovers to competitors are regarded as an important aspect of the innovation process. While a company possibly benefits from incoming information on successful R&D conducted by other companies, a generally high probability of leakage of knowledge in an industry will negatively affect profitability. This paper presents the results of an empirical study on the effects of outgoing and incoming spillovers on firms? profitability. It turns out that the expected asymmetry is actually at work. In contrast to spillovers from competitors, spillovers from suppliers, customers and research institutions exert no effect.
Keywords: O32; O31; L12; 330; Innovation; Spillover; Profitability; Innovation; Wissenstransfer; Industrielle Forschung; Unternehmen; Rentabilität; Deutschland